Biodiversity conservation in cacao agroforestry: medium-sized project - Global Environmental Facility, Oficina San José (Costa Rica) (2000)
This project is closely linked to the Action Plan of the Costa Rican National Biodiversity Law of April 14, 1998 (No. 12635) on the sustainable use of biodiversity (food security, ecosystem conservation and the improvement of living standards, particularly of rural, indigenous communities). Project activities also comply with Forestry Law No. 7575, approved in 1996 (conservation of forest ecosystems and incentives for conservation) and follow the principles of the Indigenous Law No. 6172 (priority to development within indigenous reserves and communities, technical capacity-building, and institutional strengthening of indigenous organizations). The project is also highly compatible with current activities of the Ministry of Environment and Energy (MINAE) and the National Institute for Biodiversity (INBio) at the national level and in the project area (Limon Province, Municipalities of Talamanca and Siquirres) that support biodiversity conservation both inside and outside of the proposed project area. According to the 1996 GRUAS report (GEF/UNDP/MINAE) which delineates existing biological corridors in Costa Rica, the conservation of the Talamanca-Caribbean corridor is critical for protecting biodiversity along the Atlantic Coast of Costa Rica because it is an area of high biological diversity and serves as a continuation of the Mesoamerican Biological Corridor (MBC).